Individual and Situational Predictors of Threatening Dream Content During the COVID‐19 Pandemic - Loukola, Ville; Tuominen, Jarno; Malinen, Eveliina; Tienhaara, Katariina; Olkoniemi, Henri; Revonsuo, Antti; Valli, Katja (Wiley, 2026)
Previous studies have examined how the COVID-19 pandemic affected dream recall, dream content, and nightmares. However, relatively little attention has been devoted to the individual and situational factors associated with pandemic-induced changes in dreams. The threat simulation theory of dreaming predicts that threatening situations in our waking life (situational factors) influence threatening dream content. At the same time, individual differences predispose some people to be more prone to experiencing threatening dreams more frequently than others. Using a large Finnish sample of prospective dream diaries, we analysed the relative importance of individual (e.g., belonging to a COVID-19 risk group, life satisfaction, depression and anxiety symptoms) and situational factors (e.g., daily COVID-19 worry, COVID-19 media consumption, negative and positive emotions) to determine the best predictors for threatening events and COVID-19-related threatening events in dreams. Random forest analyses revealed that individual factors were consistently better predictors than situational factors for both threatening events and pandemic-related threatening events in dreams. Lower life satisfaction was the only statistically significant predictor of threatening events and experiencing fewer positive emotions in the past 2 weeks was the only statistically significant predictor of pandemic-related threatening events in dreams. These findings suggest that the propensity to experience threatening dream content, including pandemic-related threatening events, is more of a stable trait rather than a daily fluctuating feature of dreams. In light of the threat simulation theory, it could be argued that individual variation in the proneness to simulate threatening events adaptively interacts with daily experiences to modulate threatening dream content.